A nine-family classification of caecilians (Amphibia: Gymnophiona) - Wilkinson, Mark; San Mauro, Diego; Sherratt, Emma; Gower, David J. (Zootaxa, 2011)
We propose a new family-level classification of caecilians that is based on current understanding of phylogenetic relationships and diversity. The 34 currently recognised genera of caecilians are diagnosed and partitioned into nine family-level taxa. Each family is an hypothesised monophylum, that, subject to limitations of taxon sampling, is well-supported by phylogenetic analyses and is of ancient (Mesozoic) origin. Each family is diagnosed and also defined phylogenetically. The proposed classification provides an alternative to an exclusive reliance upon synonymy in solving the longstanding problem of paraphyly of the Caeciliidae.